Biocontrol of Fusarium Crown and Root Rot and Promotion of Growth of Tomato by Paenibacillus Strains Isolated from Soil - Xu, Sheng Jun (The Korean Society of Mycology, 2014)
In this study, bacterial strains were isolated from soils from 30 locations of Samcheok, Gangwon province. Of the isolated strains, seven showed potential plant growth promoting and antagonistic activities. Based on cultural and morphological characterization, and 16S rRNA gene sequencing, these strains were identified as Paenibacillus species. All seven strains produced ammonia, cellulase, hydrocyanic acid, indole-3-acetic acid, protease, phosphatase, and siderophores. They also inhibited the mycelial growth of Fusarium oxysporum f. sp. radicis-lycopersici in vitro. The seven Paenibacillus strains enhanced a range of growth parameters in tomato plants under greenhouse conditions, in comparison with non-inoculated control plants. Notably, treatment of tomato plants with one identified strain, P. polymyxa SC09-21, resulted in 80.0% suppression of fusarium crown and root rot under greenhouse conditions. The plant growth promoting and antifungal activity of P. polymyxa SC09-21 identified in this study highlight its potential suitability as a bioinoculant.